Supporting Hope and Prognostic Information: Nurses’ Perspectives on Their Role When Patients Have Life-Limiting Prognoses - Reinke, Lynn F. (2010)
CONTEXT: Clinicians often feel challenged by the need to deliver difficult prognostic information to patients with a life-limiting illness while, at the same time, supporting their hopes. Few studies have examined nurses’ perspectives on their roles in meeting these patient and family needs. OBJECTIVES: Our objectives were to 1) describe nurses’ perspectives on meeting patients’ needs for hope and illness information; and 2) offer insights for interventions designed to improve communication about end-of-life care for patients and their families. METHODS: Using experienced interviewers, we conducted one-on-one, semi-structured interviews with 22 nurses caring for patients with advanced chronic obstructive pulmonary disease or cancer. Interviews were analyzed using a limited application of grounded theory. RESULTS: Three themes emerged: 1) Nurses support patients' hopes by understanding individual aspects of these hopes, focusing on patient quality of life, and building trust with patients; 2) Nurses provide prognostic information by assessing what the patient knows and following their lead. Nurses report doing these two activities independently; and 3) Nurses identify activities associated with the provision of prognostic information that required collaboration with physicians. Important barriers that complicate effective discussion of prognosis with patients and families were identified. CONCLUSIONS: Nurses describe behaviors that are useful when meeting patients’ and families’ needs for hope and which they are comfortable implementing in practice, without collaboration with other clinicians. By contrast, most behaviors related to meeting patients’ and families’ needs regarding prognostic information are completed collaboratively with physicians. These findings provide insight for the development of interdisciplinary interventions targeting communication around end-of-life care.